Adoption and use of Assistive Technology in Specialized Educational Assistance – AEE (Human Factors in Design, 2023)
The adoption and use of Assistive Technology – AT in Specialized Educational Assistance are essential to favor the inclusion of students with disabilities, since they provide access, permanence and participation, by allowing or expanding functionality in school context. A case study was carried out in two stages: retrospective, documental, referring to the analysis of institutional documents; and prospective, exploratory, related to interviews. It aimed to evaluate whether AT was present in the planning and in the care reports and how it was used in the AEE. It was evidenced that AT is present in the daily life of the AEE, but they are not described in the institutional documents.
Keywords: Assistive Technology; Specialized Educational Service; Planning; Report; Inclusion